AI, Society and Environment: a Possible Complex System Framework - Costa, Kleyton da; Modenesi, Bernardo; Blay, Enio Alterman; Munoz, Cristian (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência Artificial, 2024)
The large-scale deployment of AI models introduces significant uncertainty regarding their systemic behaviour. While these models have the potential to boost productivity and advance fields such as health and climate science, they also pose risks, including the reinforcement of biases, the spread of misinformation, and support for autocratic regimes. This paper examines the interaction between social, environmental, and AI systems from the perspective of a complex system’s agent framework, using a resource-impact lens to explore these dynamics.